2007
DOI: 10.1086/521519
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Dark Matter and Gas Fraction in Relaxed Galaxy Groups with X‐Ray Observations fromChandraandXMM‐Newton

Abstract: We present radial mass profiles within $0:3r vir for 16 relaxed galaxy groups-poor clusters (kT range 1Y3 keV ) selected for optimal mass constraints from the Chandra and XMM-Newton data archives. After accounting for the mass of hot gas, the resulting mass profiles are described well by a two-component model consisting of dark matter, represented by an NFW model, and stars from the central galaxy. The stellar component is required only for eight systems, for which reasonable stellar mass-to-light ratios (M/L … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
253
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(297 citation statements)
references
References 114 publications
43
253
1
Order By: Relevance
“…Fortunately there is some overlap between our groups and those of Sun et al (2009) and also Gastaldello et al (2007 , we found that on average our temperatures are in agreement (10 log T −log T Sun = 1.09 +0.13 −0.12 ). Differences in the individual cluster temperatures may be caused by the different temperature determinations applied.…”
Section: Discussionmentioning
confidence: 52%
“…Fortunately there is some overlap between our groups and those of Sun et al (2009) and also Gastaldello et al (2007 , we found that on average our temperatures are in agreement (10 log T −log T Sun = 1.09 +0.13 −0.12 ). Differences in the individual cluster temperatures may be caused by the different temperature determinations applied.…”
Section: Discussionmentioning
confidence: 52%
“…This model has been shown to be an adequate fit to the mass profiles of many morphologically relaxed systems (e.g., Pratt & Arnaud 2002;Pointecouteau et al 2005;Vikhlinin et al 2006;Gastaldello et al 2007). We emphasise that for the present investigation we use it only as a convenient fitting formula that allows direct comparison with the equivalent weak lensing parameterisations.…”
Section: Concentrationmentioning
confidence: 99%
“…The knowledge of these components has been growing thanks to the many efforts involved in collecting suitable blank sky fields to be used as template background by the XMM-Newton users [4,5], the analysis of the XMM-Newton Guest Observer Facility leading to the XMMNewton Extended Source Analysis Software [6,7], the efforts of the XMMNewton SOC 1 and the contributions of various research teams, among them our in Milan has been particularly active on this topic [8,9,10]. A summary table of the EPIC instrumental background components is available at this link 2 .…”
Section: The Current Knowledge Of the Xmm-newton Backgroundmentioning
confidence: 99%